2016
DOI: 10.1071/an14770
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of a novel phytogenic feed additive: effects on nutrient metabolism, antioxidant status and immune response of goats

Abstract: Fifteen adult Jamunapari goats (12–14 months; 18.83 ± 0.83 kg) were used to ascertain the effect of a phytogenic feed additive (PFA) on nutrient utilisation, metabolic profile, antioxidant status and immune response. The goats, randomly assigned to three groups, were fed a standard diet supplemented with the PFA at 0 (CON), 2 (PFA-2) and 3 (PFA-3) % of feed intake for a period of 60 days. Bodyweight and feed intake were recorded. At the end of the experiment, a metabolism trial was conducted. Blood was collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 45 publications
0
16
1
Order By: Relevance
“…Reduced glutathione (GSH) activity in packed RBC was measured by 5, 5-dithiobis-(2-nitro-benzoic acid; DTNB) method as per the procedure of Prins and Loos [ 42 ]. Where, the haemolysate and RBC suspension were prepared from whole blood as per the standard protocol [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Reduced glutathione (GSH) activity in packed RBC was measured by 5, 5-dithiobis-(2-nitro-benzoic acid; DTNB) method as per the procedure of Prins and Loos [ 42 ]. Where, the haemolysate and RBC suspension were prepared from whole blood as per the standard protocol [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were collected from the cephalic vein of dogs in two separate vials (with heparin and acid dextrose citrate; ACD) for estimating erythrocyte antioxidants and blood metabolites before and after each feeding period and processed as detailed elsewhere ( 14 ) . Blood samples collected in ACD were centrifuged at 2000 g for 20 min after being refrigerated for 2 h to harvest the erythrocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies [8,9] have shown that some plants containing saponins, flavonoids and polysaccharides can improve antioxidant status, ruminal fermentation, immune response and productive performance in sheep. Likewise, some HM containing saponins, flavonoids and tannins have been shown to have a positive impact on nutrient utilization efficiency in goats [10]. Other products containing saponins have shown positive impact on energy metabolism and on the duodenal flux of amino acids [11], ruminal fermentation rate [12,13], rumen microbial populations [14], and production of volatile fatty acids [12][13][14].…”
Section: Introductionmentioning
confidence: 99%